Case Study of a State-Owned Company: How does Centralized Procurement affect Operational Risk? - Mahardika Dwi Jayanti (Eduvest - Journal of Universal Studies, 2024)
This study aims to understand that the restructuring of the BUMN has a significant impact on the operational activities of the NUMN, along with its risks. The researchers used data saving from the procurement centralization process as an indication of the company's operational activities before and after restructuring. While variabel current risk exposure to indicate the conditions of the company's operational risk. Procurement centralization mechanisms tend to change before and after restructuring. So it gives the contractor his own sentiment about the operational risks and obstacles in the process. The data used refers to the company's monitoring report. Modeling between saving and current risk exposure uses double regression analysis. The results also indicate that changes in procurement centralization mechanisms have a significant impact on the company's operational risk. So in order to meet risk mitigation, the company should specifically regulate the mechanism of centralization of procurement between business groups.